Collaborative Policy Innovation for Accelerating Land Acquisition in the Economic Hub of Indonesia - Marhendra, R Agus; Aminah, Siti; Burhanuddin, Burhanuddin; Rahman, Aulia (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2025)
Land acquisition for the public interest in Indonesia frequently encounters complex bureaucracy, inefficiencies, and community resistance, which impede the implementation of National Strategic Projects (NSPs). This study examines policy innovation in land acquisition through multi-stakeholder collaboration in South Sulawesi Province, where Makassar is the provincial capital and the economic hub of eastern Indonesia. The analysis also highlights urban expansion into Gowa Regency, which heightens both the urgency and the complexity of land provision for infrastructure projects. Using a qualitative case-study design, data were gathered through in-depth interviews, participant observation, and documentary analysis. The findings indicate that collaborative approaches expedite land acquisition, improve transparency, and reduce the risk of social conflict. Models that involve central and local government, private-sector actors, community representatives, and facilitation forums have proved effective in strengthening legitimacy and trust. Strategic recommendations include institutionalising facilitation forums, advancing digital transformation in land-acquisition governance, and reformulating compensation schemes to ensure equity and accountability. By embedding collaboration, transparency, and fairness, the study contributes to more inclusive and responsive public policy while supporting the sustainability of NSPs. It also aligns with the Sustainable Development Goals (SDGs)—notably Goal 9 on resilient infrastructure, Goal 11 on sustainable cities and communities, and Goal 16 on strong institutions—offering practical pathways for inclusive and sustainable development.